The fallout - Bodeen, S. A. (Stephanie A.), 1965-; Bodeen, S. A. (Stephanie A.) , 1965- (New York : Feiwel and Friends, 2013)
After escaping the compound where Eli and his family were kept for six years by his father, they slowly make their way back into the world, but are watched wherever they go.
Horn Book
Booklist
12-19.
7-12.
HL 580
Keywords: Survival -- Juvenile fiction; Deception -- Juvenile fiction; Psychopaths -- Juvenile fiction; Fathers and sons -- Juvenile fiction